Optimizing Bone Defect Reconstruction—Balanced Cable Transport With Circular External Fixation. Issue 10 (October 2017) - Quinnan, Stephen Matthew; Lawrie, Charles
Abstract : Summary: Distraction osteogenesis has proven effective in the management of tibial bone loss from severe trauma and infection. Unfortunately, pain and scarring from wires and half pins dragging through the skin and the required prolonged time in the external fixator make treatment difficult. Cable bone transport has been shown to improve cosmesis and decrease pain during transport. However, the published methods have limitations in that they have poor control of transport segment alignment, do not allow for lengthening of the limb, and do not permit weight bearing during the treatment process. We describe a novel method of cable bone transport that addresses each of these limitations with excellent control of alignment including the transport segment, easy conversion to allow limb lengthening, and full weight bearing throughout the treatment process. In addition, the method facilitates multifocal transport and safe conversion to intramedullary nail fixation, both of which can be used to substantially shorten the time of reconstruction. Abstract : Supplemental Digital Content is Available in the Text.